النظام القانوني لشركة التوصية البسيطة - الرتمي ،نجاة; شطي ،سعاد; شكو ر ،و ردة (جامعة الوادي, 2024)
تناو لت هذه الدراسة النظام القانو ني لشركة التو صية البسيطة و التي تعتبر من شركات االشخاص بحيث تخضع ألحكام خاصة تنظمها، و تتميز بأنها تضم نو عين من الشركاء، شركاء متضامنين مسؤ و ليتهم غير محدو دة أي يسال الشريك المتضامن عن ديو ن الشركة كما كانت ديو نه الشخصية، مسؤ و لية تضامنية و نو ع ثاني من الشركاء مو صو ن تكو ن مسؤو ليتهم محدو دة بالقدر الحصة التي ساهمو ا فيها. و نظرا للمسؤ و لية المحدود دة للشركاء المو صين فانه يفرض عليهم التزام بعدم التدخل في تسيير الشركة، و يعتبر مبدأ حظر الشريك المو صى من التدخل في التسيير خاصية تميزهم عن الشركاء المتضامنين في حين يجو ز له القيام بأعمال الرقابة الخاصة بالمستندات و الحسابات أي القيام بالرقابة الداخلية. This study dealt with the legal system of the limited partnership company, which is considered a partnership of persons and is subject to special provisions regulating it. It is distinguished by the fact that it includes two types of partners: general partners whose liability is unlimited, that is, the general partner is responsible for the company’s debts as they were his personal debts, joint liability and a second type. Of the limited partners, their liability is limited to the amount they contributed. Given the limited liability of limited partners, an obligation is imposed on them not to interfere in the management of the company. The principle of prohibiting a limited partner from interfering in management is considered a characteristic that distinguishes them from general partners, while he may carry out oversight work related to documents and accounts, that is, carry out internal control.
ماستر اعمال